Raman Spectroscopy and Imaging Techniques Applied to Neolithic Artefacts as a Valuable Contribution to the Archaeological Research on Piacentine Sites - Laura Fracasetti; Sara Pescio; Maria Maffi; Paola Mazzieri; Patrizia Fumagalli; Michele Zucali; Luca Trombino (Applied Sciences)
Archaeologists and conservation scientists join interdisciplinary projects aiming at the in-depth analysis of artefacts and the resolution of new archaeological issues, overcoming the common limits of mesoscopic observation. The aim of this research is to perform multidisciplinary research, adapting imaging techniques (RTI imaging and 3D photogrammetry) and Raman spectroscopy from their conventional field of application to study and valorise neolithic archaeological findings from Piacentine sites (Emilia-Romagna, Italy). RTI images enable the detection of a comprehensive framework of anthropic and natural traces on the object surfaces to support the hypothesis of the intended usage of artefacts. Combining qualitative and quantitative Raman spectra analysis, the specific lithological characterisation of each fragment is conducted, thereby the understanding of their probable geographic provenance is enhanced. This contributes to the identification of the External Ligurian Units as a possible primary supply area, along with the already known outcrops in the Mont Viso Massif and Voltri Group. Their potential as a powerful instrument for conservation and valorisation has been revealed by 3D models. In fact, they may enrich museum exhibits, enhancing visitors’ experience through interactive engagement and guarantee the examination of artefacts by experts across the globe through online sharing, without the need for transportation and excessive manipulation.